Side-chain-type quaternized naphthalene-based poly(arylene ether ketone)s for anhydrous high temperature proton exchange membranes. Issue 101 (17th October 2016) - Li, Guibin; Zhao, Chengji; Zhu, Chongyi; Ru, Chunyu; Li, Xuefeng; Qi, Duo; Wei, Yuxue; Na, Hui
Abstract : The PA/Q-SCT-NPAEK-xx membranes with good proton conductivity, mechanical and thermal stabilities were prepared successfully. Abstract : Novel side-chain-type naphthalene-based poly(aryl ether ketones) with quaternary ammonium groups (Q-SCT-NPAEK) were synthesized and doped with phosphoric acid (PA), which can be used as potential high temperature proton exchange membranes. The PA doped Q-SCT-NPAEK membranes showed high thermal stabilities and high glass transition temperatures ( T g > 228 °C). They all have high tensile strengths, which were higher than 72 MPa. The introduction of a naphthalene moiety greatly improves the PA doped membranes' mechanical and thermal stabilities, which are much better than the commonly reported PA doped polybenzimidazole membrane. PA doped Q-SCT-NPAEK-100% with the highest IEC exhibits the highest weight uptake (635 wt%), doping level (16.6) and proton conductivity (46 mS cm −1 at 160 °C). Interestingly, these PA doped membranes still possess high thermal and mechanical stabilities, reaching up to 285 °C ( T 5% ) and 15 MPa, respectively.